Associations Between Pre‐Existing Cardiovascular Disease and Survival in Patients on Immune Checkpoint Inhibitor Therapy - Aditya Mahadevan; Aidan Vosooghi; Jagmeet Arora; Jeffrey Jones; Maziar Moslehyazdi; Warren A. Chow (Cancer Medicine, 2025)
ABSTRACT Background The impact of baseline cardiovascular disease (CVD) on survival in patients undergoing immune checkpoint inhibitor (ICI) therapy is not well understood. Therefore, we sought to determine the relationship between baseline CVD on mortality in patients undergoing ICI monotherapy or combination therapy. Methods Using TriNetX, a global database of over 120 million patients, we identified 27,820 patients with pre‐existing cardiovascular disease prior to starting ICI monotherapy and an equal number of corresponding matched controls. Results Systolic heart failure (HR: 1.38, 95% CI: 1.29–1.48), diastolic heart failure (HR: 1.34, 95% CI: 1.27–1.42), and atrial fibrillation/flutter (HR: 1.24, 95% CI: 1.19–1.29) had the greatest associations with mortality across ICI monotherapy. Conclusion Future trials of patients initiating ICI therapy should capture these baseline values to guide risk assessment, pretreatment optimization, and surveillance strategies prior to treatment initiation.